A Historical Approach to Social Studies Laboratory Method - James Mauch; Bulent Tarman (Research in Social Sciences and Technology, 2016)
In the early years of Social Studies education, great attention was given to "Social Studies Laboratories" and a teaching and learning pedagogy called "The Laboratory Method" This study examines historical documents about the development of the social studies laboratory. The researchers examined certain periodicals published in the US such as Education, The Historical Outlook and The History Teacher's Magazine along with the non-experimental historical research methodology. In an age of inquiry-based projects and "hands-on" approaches to the learning of Social Studies, a brief historical overview of the foundations of such approaches in the Social Studies seems appropriate from US perspective. Parallels are drawn by using comparative approach, and suggestions made, for a twenty-first century approach to a Social Studies Laboratory and a Laboratory Method of teaching the many disciplines that define the Social Studies. The findings of this study indicate that despite the social studies classroom, method and laboratory may have changed a great deal over the past century, the goals of the social studies teacher have not changed. The social studies teacher still works to keep his or her students actively engaged in learning, still works to help them learn new concepts and skills, and still works to help each and every student succeed. Above all, the social studies teacher still looks for strategies and tools to help students prepare for life outside of the classroom. In conclusion, a valuable lesson is to be learned from the early development of the social studies laboratory: the room, the technology and the innovative ideas are meaningless unless accompanied by a commitment to move toward student-centered activities and learning, a twenty-first century version of the "laboratory method". It is when technological access becomes inexorably entwined with teaching strategies that empower students to use, develop and critique the technology that substantive learning takes place in the social studies classroom.